Crowdworking: world experience and its implementation in the Republic of Belarus - Kogan, Anna A. (Journal of the Belarusian State University. Economics, 2020)
The participation of the Republic of Belarus in the global processes of economy digitalization is causing the transformation of labour relations, in particular, the development of the phenomenon of crowdfunding. Therefore, the object of research is the current trends of crowdfunding and the experience of the global web platforms functioning for the Republic of Belarus.